Keselarasan Konstitusionalitas Program Pensiun Tambahan dalam Kerangka Hukum Pengembangan dan Penguatan Sektor Keuangan - Rasidi, Ameliya; Alfath, Tahegga Primananda (Legal Standing : Jurnal Ilmu Hukum, 2025)
The additional pension program mandated in Article 189 paragraph (4) of Law Number 4 of 2023 concerning the Development and Strengthening of the Financial Sector (UU PPSK) aims to improve old-age protection for workers and harmonize existing pension programs. However, the discourse on wage deductions to pay additional pension contributions has raised concerns among workers, especially those with middle to lower incomes. This study examines the constitutionality of the additional pension program and the forms of legal protection for people who are unable to pay contributions. The research method used is normative legal research with a statutory and conceptual approach. The results show that the additional pension program has the potential to conflict with citizens' constitutional rights to social security and decent work. Legal protection for people who are unable to pay contributions can be carried out through government supervision, administrative sanctions, and efforts to restore participant rights. However, the implementation of the additional pension program still faces significant challenges, such as weak fundamental economic conditions and potential overlap with the existing social security system. Regulatory harmonization, strengthening supervision, and focusing on optimizing existing programs are needed to ensure the effectiveness of pension programs in ensuring the welfare of all Indonesian workers.